Vancomycin Area Under the Curve to Predict Timely Clinical Response in the Treatment of Methicillin-resistant Staphylococcus aureus Complicated Skin and Soft Tissue Infections. (27th July 2020) - Alosaimy, Sara; Murray, Kyle P; Zasowski, Evan J; Morrisette, Taylor; Lagnf, Abdalhamid M; Lodise, Thomas P; Rybak, Michael J
Abstract: Introduction: Although recent guidelines have recommended monitoring vancomycin (VAN) area under the curve (AUC)/minimum inhibitory concentration (MIC) to ensure clinical efficacy and minimize toxicity in methicillin-resistant Staphylococcus aureus (MRSA) for various infections, there are no recommendations regarding complicated skin and soft tissue infections (cSSTIs). We aimed to evaluate the association between VAN AUC and clinical outcomes in MRSA cSSTIs. Methods: This was a retrospective cohort study of adult patients treated with ≥72 hours of VAN for MRSA cSSTI from 2008 to 2013 at Detroit Medical Center. The primary outcome was timely clinical success (TCS) defined as (1) resolution of signs and symptoms of infection within 72 hours, (2) stabilization and/or reduction in lesion size, (3) alternative agents not required due to VAN failure or toxicity as elected by the prescribing clinician. Classification and regression tree (CART) analysis was performed to determine the AUC associated with TCS in the cohort. Multivariable logistic regression was used to evaluate the association between VAN-AUC and the primary outcome. Results: A total of 154 patients were included in this analysis. CART identifed an AUC ≥435 mg*hr/L for TCS. Overall, 60.9% of patients experienced TCS; 69.7% in the target-AUC group versus 52.5% in the below-target AUC group, ( P = .013). Target-AUC attainment was independently associated with increased odds of TCS (adjusted odds ratio [aOR], 2.208; 95% confidence interval [CI], 1.047–4.659). Conclusions: In adults treated with VAN for MRSA cSSTI, target-AUC attainment was independently associated with improved clinical outcomes and maybe most warranted for patients at high risk of VAN failure or VAN-associated toxicity. Abstract : In adults treated with Vancomycin (VAN) for methicillin-resistant Staphylococcus aureus Complicated Skin and Soft Tissue Infection, target-Area Under the Curve attainment was independently associated with improved clinical outcomes and maybe most warrated for patients at high risk of VAN-failure or VAN-associated toxicity.